"The importance of preoperative evaluations prior to pediatric otorhinolaryngological surgery". (December 2020) - Pallarés Martí, Beatriz; Oishi, Natsuki; Alba, José Ramón; García Callejo, Francisco Javier; Zapater, Enrique
Abstract: Objective: To describe the results of preoperative evaluations prior to pediatric surgery. Materials and methods: We reviewed a total of 99 patients, with mean age of 6.53 + 2.39 years, an average of 11.04 months after their inclusion on the surgical treatment list. These patients were obtained from General University Hospital of Valencia surgery waiting list between October 2015 and July 2016. We have reassessed all the patients before their surgery date and analyzed the results: the indication had changed or not. In the case of indication changed, the outcome was subdivided into: extension, reduction, or surgery no indicated because a clinical resolution. Results: After waiting on the list for surgery for an average of 11 months, the initial surgical indication had changed in 52 patients (52%), this groups was subdivided into: 33 patients (33%) had spontaneously resolved by the time of their reassessment and their clinical symptoms no longer met the criteria for surgery, the indication for surgery was extended in 10 patients (10%) and was reduced another 9 patients (9%). We found a statistically significantrelationship (p = 0.034) between the age of the patients at the time of the preoperative re- evaluation and modifications made to the initial surgery indication. Conclusions: Our results show the dynamic evolution of benign Waldeyer-ring related pathologies in the pediatric population due to physical growth and immune development. The clinical evaluation prior to benign pediatric surgery is recommended In specially in the group over 5 years.